Evaluation of Body Lotion from Seaweed (Kappaphycus alvarezii) and Jicama (Pachyrhizus erosus) - Ginanjar Pratama; Azni Novshally; Azwin Apriandi; Made Suhandana; Aidil Fadli Ilhamdy (JURNAL PERIKANAN DAN KELAUTAN, 2020)
The combination of natural ingredients derived from the sea and land for cosmetics has not been done much. Natural ingredients that are known to have good properties for the skin are jicama and seaweed so the objective of this study was to formulate seaweed (Kappaphycus alvarezii) and jicama (Pachyrhizus erosus) as a body lotion. The objective in this study was to determine the best body lotion preparations from seaweed (K. alvarezii) and jicama (P. erosus). The combination of seaweed and jicama as much as 15% with the formulation of seaweed and jicama were F1 (1:2), F2 (1:1), and F3 (2:1) with Completely Randomized Design, respectively. Organoleptic test results from body lotion including aroma, color, texture, and absorption in all treatments were not significantly different, except in controls. In all treatments, the type of emulsions was O/W and homogeneous. The pH values at F0, F1, F2, and F3 were 7.82; 7.97; 8.04 and 8.09. The viscosity test results found that the best treatment was F1 (16,941 cPs), while for antioxidant activity was the F3 treatment (1,656 µg/ml). Based on antioxidant performance, it was best to treat F3 for body lotion from K. alvarezii seaweed and jicama powder.